Treating low back pain in athletes: a systematic review with meta-analysis - Thornton, J. S.; Caneiro, J. P.; Hartvigsen, J.; Ardern, C. L.; Vinther, A.; Wilkie, K.; Trease, L.; Ackerman, K. E.; Dane, K.; McDonnell, S.-J.; Mockler, D.; Gissane, C.; et al. (British Journal of Sports Medicine, 2021)
The IOC has proposed standard methods for recording and reporting of data for injury and illness in sport. The IOC consensus statement authors anticipated that sport-specific statements would provide further recommendations. This statement is the tennis-specific extension of the partner IOC statement. The International Tennis Federation Sport Science and Medicine Committee, in collaboration with selected external experts, met in June 2019 to consider athlete health monitoring issues specific to tennis. Once the IOC consensus statement was finalised, the tennis-specific consensus was drafted and agreed on by the members over three iterations. Compared with the IOC consensus statement, the tennis consensus contains tennis-specific information on injury mechanism, mode of onset, injury classification, injury duration, capturing and reporting exposure, reporting risk and study population. Our recommendations apply to able-bodied as well as wheelchair tennis players. Where applicable, specific recommendations are made for wheelchair tennis.